Development of a sensitive, direct enzyme immunoassay for progesterone determination in follicular fluid from individual buffalo ovarian follicles - PRAKASH, B S; PALTA, P; BANSAL, N; MANIK, R S; MADAN, M L (The Indian Journal of Animal Sciences, 2013)
A simple, highly sensitive, direct enzymeimmunoassay (EIA) on microtitre plates was developed and validated for progesterone estimation in follicular fluid obtained from buffalo ovarian follicles. The heterologous EIA made use of antiprogesterone-7 IX -carboxyethylthioether-BSA as the antibody and progesterone-6 6-hydroxyhemisuccinate- horse radish peroxidase (HRP) as the enzyme labe1. The lowest detection limit ofEIA which requires 0.05 ul follicular fluid was 0.4 pg/well, and the sensitivity was 5.5 pg/well at 50% binding. In terms of mid-point sensitivity.EIA was 10-times more sensitive than radioimmunoassay (RIA): Progesterone estimates from buffalo ovarian follicular fluid samples in EIA showed high correlation (r = 0.95) with RIA values (n = 32) and the concentrations obtained in the 2 procedures were similar. Mean progesterone concentrations (nglml) in medium (57.31 Â± 6.31) and large follicles (43.26 Â± 6.94) were significantly higher (P